Design of Thermoresponsive Polymers with Aqueous LCST, UCST, or Both: Modification of a Reactive Poly(2-vinyl-4,4-dimethylazlactone) Scaffold - Zhu, Y.; Batchelor, R.; Lowe, Andrew; Roth, P. (2016)
© 2016 American Chemical Society. The synthesis and aqueous solution properties of a family of zwitterionic homo-, co-, and terpolymers derived from poly(2-vinyl-4,4-dimethylazlactone) (pVDMA) with tunable lower and upper critical solution temperatures (LCST and UCST) are presented. A RAFT-made pVDMA precursor was reacted with mixtures of zwitterionic sulfopropylbetaine (SPB) amine or sulfobutylbetaine (SBB) amine, tetrahydrofurfurylamine (THF amine), and benzylamine (Bz amine) in varying molar ratios. Products were characterized by variable temperature (VT) NMR spectroscopy, FT-IR spectroscopy, size exclusion chromatography, turbidity, and VT dynamic light scattering in order to confirm quantitative postpolymerization modification, determine molar compositions, and elucidate structure-property relationships. Polymers comprising large molar fractions of THF groups showed LCST behavior due to a polarity change of the THF-functional segments, while SPB/SBB-rich samples, including the zwitterionic homopolymers, showed UCST behavior in ultrapure water based on electrostatic polymer-polymer attractions. Binary SPB-THF copolymers were water-soluble between 0 and 90 °C for a large compositional range. Terpolymers comprising molar SPB:THF:Bz ratios of approximately 50:25:25 showed a low LCST and a high UCST (LCST < UCST) with a miscibility gap in which the SPB groups and THF groups were not fully hydrated. In the one-phase regions below the LCST and above the UCST, polymer chains were presumed to be unimerically dissolved with partially solvated domains undergoing intrachain associations. Addition of NaCl caused LCST and UCST behavior to disappear, resulting in temperature-independent solubility. Molecular insights presented herein are anticipated to aid in the development of smart materials with double LCST < UCST or UCST < LCST thermoresponsiveness.